UJI BEBERAPA KONSENTRASI EKSTRAK DAUN MIMBA (Azadirachta indica A. Juss) UNTUK MENGENDALIKAN LARVA Lamprosema indicata F. PADA TANAMAN KEDELAI (Glycine max L. Merill) - Desita Salbiah; Nelly Andria (DINAMIKA PERTANIAN, 2019)
The Lamprosema indicata Fabricius larvae is one of the main pests in soybean plantations, which cause up to 80% damage. The alternative control is the use of neem Leafs (Azadirachta indica A. Juss) which have the potential as a botanical insecticide. This research aims to find out the effective concentration of neem Leafs extract to control Lamprosema indicata F. larvae on soybean (Glycine max L. Merill). The research was conducted at the Laboratory Plant Pest and Experimental Farm in the Faculty of Agriculture, University of Riau from May to October 2018. The research was carried out by using a completely randomized design (CRD) with 6 treatments and 4 replications to obtain 24 experimental units. Treatment consist of several concentrations of neem leafs extract 0 g.l-1 water, 20 g.l-1 water, 40 g.l-1 water, 60 g.l-1 water, 80 g.l-1 water and 100 g.l-1 water. The results showed that the concentration of 80 g.l-1 water was effective to control the L. indicata larvae with an initial death time of 5.50 hours and total mortality was 87.50%.